2017
DOI: 10.1111/are.13512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cannabis oil on growth performance, haematology and metabolism of Nile TilapiaOreochromis niloticus

Abstract: Cannabis sativa is a plant that produces an oil with psychoactive and stress reduction effects and thus illegal in many nations. Lately, the beneficial properties of the plant extract are becoming better understood and perceptions are changing. As the aquaculture industry matures from a primitive extensive pond system to an industrialized intensive system, fish stress and disease incidence are increasing, with negative economic results. A nutritional ingredient that could reduce stress and disease incidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Their results showed that prolonged exposure could contribute to oxidative and genetic damage. Experimental exposure to cannabis extracts further led to negative physiological or behavioral impacts in carp ( Cyprinus carpio L.), tilapia ( Oreochromis niloticus ), and zebrafish ( Danio rerio ) and induced high mortality rates in mosquitoes ( Aedes albopictus ) and snails ( Physella acuta ) . Still, given knowledge gaps with regard to actual Δ-9-THC and THC-COOH concentrations in aquatic ecosystems and the effects of the compounds on mussels or other organisms in the wild, it is difficult to draw broader conclusions about potential environmental risks posed by exposure to active cannabis compounds for aquatic organisms.…”
Section: Results Policy Recommendations and Discussionmentioning
confidence: 99%
“…Their results showed that prolonged exposure could contribute to oxidative and genetic damage. Experimental exposure to cannabis extracts further led to negative physiological or behavioral impacts in carp ( Cyprinus carpio L.), tilapia ( Oreochromis niloticus ), and zebrafish ( Danio rerio ) and induced high mortality rates in mosquitoes ( Aedes albopictus ) and snails ( Physella acuta ) . Still, given knowledge gaps with regard to actual Δ-9-THC and THC-COOH concentrations in aquatic ecosystems and the effects of the compounds on mussels or other organisms in the wild, it is difficult to draw broader conclusions about potential environmental risks posed by exposure to active cannabis compounds for aquatic organisms.…”
Section: Results Policy Recommendations and Discussionmentioning
confidence: 99%
“…Hemp processing by-products may have potential as new salmonid aquafeed ingredients due to their good profiles of essential amino acids and polyunsaturated fatty acid (PUFA) that are needed for fish growth and health [ 10 , 11 ]. While this may be the first effort with a focus on salmonids, encouraging results have been reported on the use of hemp proteins and oils for other commercially relevant aquaculture species such as sunshine bass, cobia, common carp, and Nile tilapia [ 12 , 13 , 14 , 15 ]. In our previous study, we reported on the characterization of triacylglycerols (TAGs) and other lipids derived from hemp by-products using UPLC-HRMS [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ωστόσο, αν και έχουν μελετηθεί αρκετά οι επιδράσεις φαρμακευτικών φυτών στον τομέα των υδατοκαλλιεργειών, οι ιδιότητες της κάνναβης στον τομέα αυτό είναι ακόμα άγνωστες. Ο αριθμός των μελετών είναι μικρός ενώ για κάποια είδη ψαριών όπως το λαβράκι (Webster et al, 2000) και η τιλάπια (O. niloticus) (Saoud et al, 2018) έχει μελετηθεί η επίδραση των σπόρων κάνναβης στην ανάπτυξη, στην επιβίωση και στη θρεπτική σύσταση αλλά και στο αιματολογικό προφίλ. Η ρίγανη (O. vulgare) είναι εγγενές φυτό της μεσογειακής χλωρίδας και ανήκει στην οικογένεια των χειλανθών (Lamiaceae family).…”
Section: φυτοβιοτικά (Phytobiotics) στις υδατοκαλλιέργειεςunclassified